Non-State Environmental Actors in Forest Governance: Greenpeace Indonesia’s Role in Addressing Deforestation - Affwa, Fadilah; Jannati, Nasywa Aisyiah Hilda; Khairunnisa, Shafa Kamila Khairunnisa; Witaloka, Tiara; Rizki, Diyah Pitaloka (SocioHumania: Journal of Social Humanities Studies, 2025)
Deforestation remains a critical environmental and socio-political challenge in Indonesia, driven by economic expansion, weak regulatory enforcement, and competing development priorities. In recent decades, forest governance has increasingly involved non-state environmental actors that operate beyond formal state authority. This study examines the role of Greenpeace Indonesia as a non-state environmental actor in addressing deforestation within Indonesia’s forest governance framework during the period 2023–2025. Employing a qualitative descriptive approach with a library research design, the study analyzes secondary data drawn from academic literature, policy documents, organizational reports, and relevant media sources. The analysis is guided by theoretical perspectives on non-state actors, environmental diplomacy, role theory, and global environmental governance. The findings demonstrate that Greenpeace Indonesia plays a strategic role as an environmental watchdog and norm entrepreneur by conducting research-based advocacy, mobilizing public opinion, and engaging in informal environmental diplomacy. Through transnational campaigns and corporate-targeted advocacy, Greenpeace contributes to shaping environmental norms and influencing both state and corporate behavior related to deforestation. However, its effectiveness is constrained by political resistance, structural power asymmetries, and limited access to formal decision-making processes. This study highlights the significance of civil society actors in forest governance and underscores the need to integrate non-state contributions into more inclusive and accountable environmental governance frameworks.